Caddisflies from Myanmar: New records and descriptions of new species (Insecta, Trichoptera) - Mey, Wolfram; Malicky, Hans (Zootaxa, 2021)
Adult Trichoptera material collected from different localities in Myanmar resulted in the detection of eleven new species which are described as Rhyacophila inwabumensis spec. nov., Hydropsyche kachinenis spec. nov., Limnocentropus rossicorum spec. nov., Lepidostoma pennicularium spec. nov., Lepidostoma indivisum spec. nov., Apatania naumanni spec. nov., Neophylax obliquostriatus spec. nov., Nothopsyche anawrahta spec. nov., Aplatyphylax bamaricus spec. nov., Aplatyphylax myanmaricus spec. nov., and Oecetis kachinomekana spec. nov. Neophylax nigripunctatus Tian & Li 1993 (in Tian et al. 1993), syn. nov. is excluded from Neophylax McLachlan 1871 and synonymized with Phylostenax himalus Mosely 1935. Plectrocnemia bifurcata Tian 1993 (in Tian et al. 1993) is synonymized with P. kainam Malicky 1993, syn. nov. Ninety-eight species are recorded from various places in Myanmar including some inadequately known taxa for which new illustrations of the male genitalia are provided.